Population Size of Indo-Pacific Humpback Dolphins (Sousa chinensis) at Khanom, Thailand - JAROENSUTASINEE, Mullica; JUTAPRUET, Suwat; JAROENSUTASINEE, Krisanadej (Walailak Journal of Science and Technology (WJST), 2011)
Indo-Pacific humpback dolphins (Sousa chinensis) were estimated with the Mark-Recapture Model from a boat-based photo-identification survey at Khanom, Nakhon Si Thammarat, Thailand from July 2008 - June 2009. Indo-Pacific humpback dolphins were encountered at a water depth of 1.1 - 7.5 m, a distance off shore of 21 - 1,021 m and water transparency of 67 - 256 cm. Groups and solitary Indo-Pacific humpback dolphins were sighted 39 times. They were extensively viewed in the coastal zone between Nang Kham bay to Thong Ching bay. There were 34 sightings of groups and five sightings of solitary individuals. A total of 49 individuals were identified and catalogued. There were 33 identified adults, eight juveniles and eight calves. The group size of humpback dolphins varied from 2 - 20 individuals. The group size of adults ranged between 2 - 12 dolphins. The juveniles group size ranged from 0 - 6 dolphins. There were no groups observed consisting solely of juveniles. Groups without juveniles were seen 8 times. The number of calves per group ranged between 0 - 4 individuals. The percentage and number of calves per group were significantly lower than the percentage and number of juveniles. The mean size of groups containing calves was larger than non-calf groups. The estimated abundance of this population from the Jolly-Seber method was 49 individuals.